Parroquia - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1962)
SPANISH: Nueva casa Parroquia de Santa Rita de Castilla 1962, La parroquia de Santa Rita de Castilla que lleva el mismo nombre del localidad, fue fundada el 7 de agosto de 1956, Santa Rita de Castilla es una localidad peruana, del distrito de Parinari, provincia de Loreto, al noroeste del departamento de Loreto. Es la capital de hecho del distrito de Parinari. Se encuentra al margen izquierdo del río Marañón.
ENGLISH: New house Parish of Santa Rita de Castilla 1962, The parish of Santa Rita de Castilla that bears the same name of the locality, was founded on August 7, 1956, Santa Rita de Castilla is a Peruvian locality, in the district of Parinari, province of Loreto, northwest of the department of Loreto. It is the de facto capital of the district of Parinari. It is located on the left bank of the Marañon River.

SPANISH: Nueva casa Parroquia de Santa Rita de Castilla 1962, La parroquia de Santa Rita de Castilla que lleva el mismo nombre del localidad, fue fundada el 7 de agosto de 1956, Santa Rita de Castilla es una localidad peruana, del distrito de Parinari, provincia de Loreto, al noroeste del departamento de Loreto. Es la capital de hecho del distrito de Parinari. Se encuentra al margen izquierdo del río Marañón.
ENGLISH: New house Parish of Santa Rita de Castilla 1962, The parish of Santa Rita de Castilla that bears the same name of the locality, was founded on August 7, 1956, Santa Rita de Castilla is a Peruvian locality, in the district of Parinari, province of Loreto, northwest of the department of Loreto. It is the de facto capital of the district of Parinari. It is located on the left bank of the Marañon River.
Parish
Keywords: Iquitos (Perú)|~|Parish--Village|~|Parroquia|~|Pueblo|~|Iquitos (Perú)